2023
DOI: 10.1111/1756-185x.14627
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib, a selective tyrosine kinase inhibitor, prevents joint destruction in rheumatoid arthritis animal model

Abstract: Aim:We aimed to evaluate the preventive role of the tyrosine kinase inhibitor dasatinib in an animal model of rheumatoid arthritis (RA).Methods: DBA/1J mice were injected with bovine type II collagen to induce arthritis (collagen-induced arthritis [CIA]). There were four experimental groups of mice, namely negative control (non-CIA), vehicle-treated CIA, dasatinib-pretreated CIA, and dasatinib-treated CIA. After collagen immunization, arthritis progression in the mice was clinically scored twice weekly for 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Extensive research has validated the inhibitory impact of numerous multitargeted tyrosine kinase inhibitors on bone resorption and loss, suggesting potential therapeutic advantages for bone disease management. For example, dasatinib has been shown to forestall joint destruction in models of rheumatoid arthritis by impeding osteoclastogenesis, while also enhancing bone volume in xenograft mice models infused with osteotropic MDA-MB-231 cells by diminishing osteoclast activity . Similarly, the tyrosine kinase inhibitor GNF-2 was observed to inhibit osteoclast differentiation by curtailing RANKL-induced NF-κB signaling, thereby offering protection against inflammation-induced bone destruction .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has validated the inhibitory impact of numerous multitargeted tyrosine kinase inhibitors on bone resorption and loss, suggesting potential therapeutic advantages for bone disease management. For example, dasatinib has been shown to forestall joint destruction in models of rheumatoid arthritis by impeding osteoclastogenesis, while also enhancing bone volume in xenograft mice models infused with osteotropic MDA-MB-231 cells by diminishing osteoclast activity . Similarly, the tyrosine kinase inhibitor GNF-2 was observed to inhibit osteoclast differentiation by curtailing RANKL-induced NF-κB signaling, thereby offering protection against inflammation-induced bone destruction .…”
Section: Discussionmentioning
confidence: 99%
“…The senescent cells displayed impaired chondrogenic differentiation ( 193 ) when compared with a non-senescent cell population, making them potential targets for senotherapeutics. Murine models of rheumatoid arthritis (RA) found that dasatinib was protective against RA by inhibiting osteoclastogenesis through immunomodulatory effects ( 194 ). Additional murine studies have shown that SC interact with synovial cells and that dasatinib and/or quercetin have been effective in ameliorating cartilage damage and pain due to OA, as well as alleviating post-menopausal osteoporosis ( 73 , 75 , 195 , 196 ).…”
Section: Senotherapeutic Potential In Veterinary Speciesmentioning
confidence: 99%
“…25,26 Moreover, while pan-JAKi will provide maximal efficacy,theycarrythegreatestriskoftoxicityduetobroadpathwaysuppression.Incontrast,selectiveJAKimaydecreaseadverse effects and increase safety and efficacy. 16,27 More and more JAKi…”
Section: Differentiatingmrhwithfeaturesmimickingdmfromadm-mrhmentioning
confidence: 99%
“…Moreover, while pan‐JAKi will provide maximal efficacy, they carry the greatest risk of toxicity due to broad pathway suppression. In contrast, selective JAKi may decrease adverse effects and increase safety and efficacy 16,27 . More and more JAKi are currently in development, so it is important to consider the balance between benefits and risks of different agents in the future.…”
Section: Author Age Y Sex Articular Features Cutaneous Features Assoc...mentioning
confidence: 99%